2019
DOI: 10.1080/17482631.2019.1659540
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of quality of life the first year after stroke in Denmark and Norway. A qualitative analysis

Abstract: Purpose: This study aims to explore quality of life (QOL) during the first year of recovery after stroke in North Norway and Central Denmark. Method: Individual in-depth interviews with 11 stroke survivors were performed twelve months after stroke onset. An interpretative, inductive approach shaped the interview process and the processing of data. Results: We found that QOL reflected the individuals’ reconstruction of the embodied self, which was identified by three intertwined and negotiating processes: a fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 56 publications
4
49
0
Order By: Relevance
“…In our study, both cohorts scored lowest in the energy domain one-year post-stroke. Fatigue is common after stroke, tends to persist, and contributes to lower QOL [49,50]. The SS-QOL is the only stroke-specific multidimensional instrument that includes this element to measure stroke-specific HRQOL, which may give the measure an advantage.…”
Section: Domains and Profiles Of The Ss-qol Scalementioning
confidence: 99%
“…In our study, both cohorts scored lowest in the energy domain one-year post-stroke. Fatigue is common after stroke, tends to persist, and contributes to lower QOL [49,50]. The SS-QOL is the only stroke-specific multidimensional instrument that includes this element to measure stroke-specific HRQOL, which may give the measure an advantage.…”
Section: Domains and Profiles Of The Ss-qol Scalementioning
confidence: 99%
“…Fatigue has been described as a state of weariness unrelated to previous exertion levels, which is usually not ameliorated by rest, and as a chronic and subjective feeling of lack of energy, weariness and aversion to effort [3]. PSF is associated with higher risk of institutionalization and death and impedes patients' rehabilitation [4] and quality of life [5]. Although fatigue in the acute phase is often considered a normal and temporary feature following stroke, Lerdal et al [6] identified fatigue in the acute phase as an independent predictor of poorer physical health 36 months after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the findings by Pallesen et al (2019) who report that stroke survivors find that they have to deal with the impairments after the stroke, but they also learn to manage and overcome challenges by being active and participating in everyday life (Pallesen et al, 2019 ). Active coping strategies have a positive impact on quality of life after stroke (Lo Buono et al, 2017 ; Ostir et al, 2008 ) and subjectively experienced wellbeing is related to the ability to manage the consequences of a stroke (Lo Buono et al, 2017 ; Pedersen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%